Experiences with Higher-Risk Myelodysplastic Syndromes and Improving Patient-Centered Treatment Decision-Making: A Qualitative Study of Patients, Caregivers, and Providers - Maravic MC; Land N; Prood N; Cagle C; May SG; Batt K; Sabate EJ; Afulezi N; Jhaveri TZ; Iraca T; Hogea C (Cancer Management and Research, 2025)
Melissa Culhane Maravic,1 Natalie Land,1 Nadya Prood,1 Claire Cagle,1 Suepattra G May,1 Katharine Batt,1,2 Eduardo J Sabate,3 Ngozi Afulezi,3 Teraneh Z Jhaveri,3 Tracey Iraca,4 Cosmina Hogea3 1Precision AQ, Bethesda, MD, USA; 2Sprouts Consulting, Ltd, Raleigh, NC, USA; 3Gilead Sciences, Foster City, CA, USA; 4The MDS Foundation, Yardville, NJ, USACorrespondence: Melissa Culhane Maravic, Email Melissa.Maravic@precisionaq.comPurpose: Research on treatment experiences and decision-making in higher-risk myelodysplastic syndromes (HR-MDS) remains limited, with most studies employing quantitative approaches. This study employed qualitative research methods to further explore patients’, caregivers’, and providers’ experiences with HR-MDS and treatment decision-making.Patients and Methods: Exploratory, qualitative web-based focus groups and interviews were conducted between April-May 2023 amongst US-based patients with HR-MDS, caregivers for a patient with HR-MDS for ≥ 3 months, and board-certified oncologists and/or hematologists who treated ≥ 5 patients with HR-MDS in the past year. Recruitment was facilitated by a survey vendor and the MDS Foundation using convenience sampling. De-identified transcripts were analyzed using constant comparative analysis to identify key themes.Results: A total of 8 patients, 6 caregivers, and 18 providers participated. Providers described challenges conveying the HR-MDS diagnosis to patients, while patients and caregivers reported lacking information regarding the condition, prognosis, and available treatment options. Providers discussed the lack of HR-MDS treatment options. Patients and caregivers were primarily concerned with treatment efficacy and ability to improve quality of life. While patients, caregivers, and providers expressed interest in shared decision-making (SDM), implementation of SDM can be influenced by the patient’s age, level of education, and health literacy. Treatment barriers included lack of treatment options, insurance coverage, lack of information sharing, and access to treatment centers. High levels of caregiver burden were reported, with caregivers having to sacrifice their social lives, assume financial responsibility, and execute the daily management of the patient.Conclusion: Findings highlight key challenges in HR-MDS including the complexities surrounding HR-MDS education and communication. Patient-centered approaches incorporating cognitively appropriate education and decision aids, and provision of supportive services are needed to improve patient-centered treatment decision-making in HR-MDS. Future research should build upon these findings amongst the broader HR-MDS population and explore practical approaches to facilitate patient-provider communication.Keywords: myelodysplastic syndromes, communication, shared decision-making, treatment burden, qualitative research, treatment decision-making